2022
DOI: 10.3389/fphar.2022.976799
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic insights elaborating the potential of retinoids in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is perceived with various pathophysiological characteristics such oxidative stress, senile plaques, neuroinflammation, altered neurotransmission immunological changes, neurodegenerative pathways, and age-linked alterations. A great deal of studies even now are carried out for comprehensive understanding of pathological processes of AD, though many agents are in clinical trials for the treatment of AD. Retinoids and retinoic acid receptors (RARs) are pertinent to such attributes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 178 publications
0
7
0
Order By: Relevance
“…The pathophysiological pathway involved changes in neurotrophic support and neuron–glia interaction, resulting in central sensitization to pain, which was linked to the same pathway in depressive and anxiety symptoms [ 34 , 39 ]. Glucocorticosteroids in the brain played an important physiological process involved in various stress-related conditions to preserve neuroplasticity within the hippocampus [ 40 ]. Research had established that the neurohormonal stress axis involving sympathoadrenal, and HPA activation played a crucial role in the onset and progression of alcoholic neuropathy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological pathway involved changes in neurotrophic support and neuron–glia interaction, resulting in central sensitization to pain, which was linked to the same pathway in depressive and anxiety symptoms [ 34 , 39 ]. Glucocorticosteroids in the brain played an important physiological process involved in various stress-related conditions to preserve neuroplasticity within the hippocampus [ 40 ]. Research had established that the neurohormonal stress axis involving sympathoadrenal, and HPA activation played a crucial role in the onset and progression of alcoholic neuropathy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a type of irreversible neurological disorder that is mainly identified among elderly people globally. Statistically, a staggering 15 million people suffer from AD worldwide, making it the most prevalent neurological condition in the world [ 1 ]. The steady increase in AD cases is partly attributed to the aging global population.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed that aberrant Aβ and tau proteins may play a significant role in AD pathogenesis. Generally, it is understood that the amyloid hypothesis of AD describes the neurodegeneration and memory deficits in AD patients due to the buildup of the Aβ plaque in the temporal lobe [ 1 ]. Consequently, these aggregates trigger numerous effects, including mitochondrial dysfunction, neuroinflammation, oxidative stress, and calcium imbalances, resulting in the loss of white matter in the brain and neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic retinoids that are structurally similar to retinol/retinoic acid are approved for dermatological indications (e.g., adapalene) and some cancers (e.g., bexarotene) 10 , 11 , as well endogenous retinoids including all- trans retinoic acid (tretinoin) and 13- cis retinoic acid (isotretinoin) used in dermatology. There is also continued interest in repurposing both endogenous and synthetic retinoids across a range of other indications, including neuropsychiatry 2 , 12 . Currently, retinol supplementation is not specifically indicated unless an individual is deficient, which is rare in high-income countries, though much more common in low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous observational or randomised controlled studies have explored the effects of supplementation, a high vitamin A diet, and/or measured circulating retinol in a variety of disease contexts. However, the data from these efforts have often either been null or conflicting between studies 12 16 . Despite this, recent observational evidence suggests a relationship between a greater circulating retinol abundance and lower mortality in a large, prospective 30-year follow-up study 17 .…”
Section: Introductionmentioning
confidence: 99%